The pedagogy of multiliteracy and multimodality through memes - Ugalingan, Gina B. (Animo Repository, 2022)
While the rise in social media use has facilitated the instantaneous exchange of ideas and has allowed for safe interaction during a global pandemic, this reliance on digital spaces has also led to a proliferation of misinformation and disinformation. This then calls for teachers to help students become digitally literate citizens who are able to read, analyze, and communicate critically. In light of this, many language education classrooms have incorporated lessons and assessment to raise students' social awareness and critical thinking. This pilot study looks into the multimodal output of university students in a general education English class to explore the application of knowledge processes of multiliteracies - experiencing, conceptualizing, analyzing, and applying (Kalantzis, Cope, 2013). A classroom activity that used memes was prepared by the researchers in order to teach logical fallacies in argumentation. It is argued that using memes to teach logical fallacies in argumentation encourages students to engage with multimodal resources. Upon careful analysis of gathered data, the following results are forwarded: memes generated by students are reflective of the multiliteracies employed in their conceptualization and execution, and the interaction between multiliteracies and multimodalities is instrumental in teaching and promoting critical thinking. Thus, this study reinforces that the multiliteracies framework is an aid for students to become critical thinkers.